Incidence of the diagnosis of factitious disorders – Nationwide comparison study between Germany and Norway - Geile, Julian (Forensic Sci Med Pathol, 2020)
Factitious disorders (FD) like Munchausen syndrome are well known to most physicians, yet the corresponding ICD-10 diagnosis F68.1 remains severely under-assigned and often misdiagnosed. To approach this problem, we conducted a nationwide inquiry for Germany and Norway as well as a comparison between these two countries regarding the incidence of diagnosis of FD. The assignment rates of F68.1 in somatic hospitals from 2008 to 2016 were analyzed based on the Diagnosis Related Groups statistic from the German Federal Statistical Office and the data provided from the Norwegian Patient Registry. The Norwegian data also included information on individual patients whereas the German data only contained the total number of F68.1 assignment due to strict medical confidentiality laws. The incidence of the diagnosis of FD in Germany and Norway showed similar assignment rates with 3.71 and 3.18 per 100,000, respectively. The mean age was 39.4 years for German patients and 35.6 years for Norwegian patients. The gender distribution was almost equal for the individual patients’ rate (49% female and 51% male). Furthermore, our results indicate that female patients with FD tend to demand healthcare services more frequently than male patients. Smaller studies focusing on the diagnosis of FD have significantly higher assignment rates compared to nationwide inquiries. Our results illustrate substantial differences between estimations of the incidence of FD and the need for further studies. Besides the many obstacles associated with diagnosis of FD, strict medical confidentiality laws prevent reliable and scientific investigations of this matter.